Challenges and recent advancements in the transformation of CO2 into carboxylic acids: straightforward assembly with homogeneous 3d metals. (28th October 2022) - Cauwenbergh, Robin; Goyal, Vishakha; Maiti, Rakesh; Natte, Kishore; Das, Shoubhik
Abstract : Transformation of carbon dioxide (CO2 ) into valuable organic carboxylic acids is essential for maintaining sustainability. In this review, such CO2 thermo-, photo- and electrochemical transformations under 3d-transition metal catalysis are described from 2017 until 2022. Abstract : The transformation of carbon dioxide (CO2 ) into useful chemicals, advanced materials, and energy is a long-standing challenge in both fundamental science and industry. In recent years, utilization of CO2 in the presence of inexpensive and non-negligible environmentally friendly 3d metal-based catalysts (Fe, Mn, Co, Ni, Cu and Ti) has become one of the most attractive topics. Particular attention has been given to the synthesis of carboxylic acids and their derivatives since these molecules serve as key intermediates in the chemical, fertilizer, and pharmaceutical sectors. Considering numerous challenges linked with CO2 reactivity, a number of research groups have recently focused on the transformation of CO2 into carboxylic acids by following thermo-, photo-, and electrochemical strategies. However, facile access to such acids remains a vital challenge in catalysis and in organic synthesis owing to the high stability of the CO2 molecule in which the carbon atom has the highest oxidation state. Another hurdle is to solve the selectivity issue caused by the reaction of different catalytic systems with CO2 in the presence of reactive functional group-containing molecules. Despite all these issues, a wide range of transition metal-based catalysts have been applied in this direction, but owing to their cheaper price and inherent reactivity, 3d metals are at the forefront in the CO2 utilization domain. Considering these, we aim to summarise recent advances (over the past five years) of 3d-metal complexes and their reactivity towards the activation of CO2 for the synthesis of carboxylic acids. Furthermore, we discuss current research trends, knowledge gaps, and invigorating perspectives on future advances.